Feminism, Writing and the Media in Spain Ana María Matute, Rosa Montero and Lucía Etxebarria - Oaknín, Mazal (Studies in Contemporary Women's Writing, 2019)
This book explores the different treatment of writing by women and writing by men in twenty-first-century Spain. Focusing on contemporary Spanish authors Ana María Matute (1926-2014), Rosa Montero (1952-), and Lucía Etxebarria (1966-), the author examines how Spanish women writers are marketed in Spain and, in particular, how current marketing strategies reinforce traditional structures of femininity. Through an analysis of their work and lives in the context of the Franco Regime, the Transition to democracy and contemporary Spain, this book provides an innovative study of the construction of the public personae of these key female writers. As social media and the internet transform authors' relationship with their readers, the rapidly shifting publishing industry offers an important context for the difficult balance between high levels of reception and visibility and the persistence of traditional gender stereotypes.